Understanding the Impact of Windstorms on Economic Activity from Night Lights in Central America - Ishizawa, Oscar A. (World Bank, Washington, DC, 2017)
Central America is particularly prone to tropical storms and hurricanes. The prevailing conditions of poverty and socioeconomic inequality in most countries of the region make their exposed population especially vulnerable to those adverse natural events. This paper quantifies the causal effects of hurricane windstorms on economic growth using night lights in the Central America region at the highest spatial resolution data available (1 square kilometer). The paper uses a unique data set of monthly night lights data to capture the temporal disaggregation of hurricanes. Hurricanes in Central America are often localized events and tend to make landfall during the final months of the year that are better captured through monthly -– rather than yearly -– frequency data. The results suggest that major hurricanes show negative effects up to 12 months after the hurricane strikes (between -2.6 to -3.9 percent in income growth at the local level). After that, the analysis finds positive effects during the second year and the first half of the third year as evidence of post-disaster recovery (from 2.5 to 3.6 percent in income growth). The paper contributes to the literature on natural disasters by providing robust estimates of the causal effects of major hurricane windstorms on Central America, which are negative (in the short term) and positive (two years after hurricanes hit).